Major, minor and trace element concentrations in spices and aromatic herbs from Sicily (Italy) and Mahdia (Tunisia) by ICP-MS and multivariate analysis - Potortì, Angela Giorgia; Bua, Giuseppe Daniel; Lo Turco, Vincenzo; Ben Tekaya, Asma; Beltifa, Asma; Ben Mansour, Hedi; Dugo, Giacomo; Di Bella, Giuseppa (Food chemistry, 2020)
•Inorganic content in spice and aromatic herb samples has been evaluated.•Levels of Pb in some samples exceed the maximum allowable level.•Differences among spices and aromatic herbs has been observed.•Discrimination between Italian and Tunisian samples was achieved by PCA.•Essential elements intake through analyzed samples was small. Element contents in different types of spices and aromatic herbs collected from Italy and Tunisia were evaluated. The aim was to evaluate: the possible differences and/or similarities among the analyzed samples; if it is possible related the samples to their geographical origins; the nutritional quality and the potential health risks. Potassium, Ca, Mg and Ni were low in laurel and rosemary; mint and thyme showed the highest Na and the lowest Se contents; arsenic and Cd levels were found highest in verbena which had also the lowest Hg content; lastly, black pepper had the highest Mn and the lowest Pb contents. Instead discrimination between Italian and Tunisian samples for each spices and aromatic herbs under analysis was achieved by PCA. Essential elements intake through samples was small. Levels of Pb in some samples exceed the maximum allowable level, but any safety risk for consumers is excluded.